Muslim Millennials and Food Choices: Unpacking the Halal Awareness Gap in Aceh, Indonesia - Arinal Rahmati; Benazir Benazir; Azharsyah Ibrahim (Jurnal Ilmiah Peuradeun, 2026)
Halal awareness constitutes a fundamental dimension of Islamic consumption, guiding Muslims in making ethical and religiously compliant choices. Despite Aceh’s strong Islamic identity and the formal implementation of Sharia law, empirical evidence indicates a persistent gap between expressed concern for halal compliance and actual consumer practices among Muslim millennials. This study examines the level of halal awareness and the socio-psychological factors influencing food purchasing behavior among millennials who consume food from non-Muslim-owned establishments in Aceh. Employing a qualitative descriptive approach, data were collected through in-depth interviews with 40 participants, complemented by observations and focus group discussions conducted across four districts: Banda Aceh, Pidie, Bireuen, and Lhokseumawe. The findings reveal that practical considerations such as trust, price sensitivity, hygiene, and customer service frequently outweigh religious verification in consumption decisions. Notably, approximately 80% of respondents demonstrated only a superficial understanding of halal certification procedures and Sharia compliance. These findings underscore a significant value–behavior gap in halal consumption within a Sharia-governed context, highlighting the need for integrated educational and regulatory interventions. The study recommends strengthening halal literacy through targeted educational initiatives, enhanced certification transparency, and digitally mediated outreach to reinforce halal integrity in Aceh’s evolving consumer landscape, with implications for other Muslim-majority societies facing similar challenges.